2017
DOI: 10.20944/preprints201711.0081.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gastrointestinal Manifestations of Marfan Syndrome

Abstract: Symptoms attributed to the gastrointestinal manifestations of multisystem disorders play an important role in the long-term management of these conditions. Gastrointestinal complications of a variety of connective tissue disorders have been studied and there is an increased interest in the incidence and prevalence of these symptoms. Descriptions of the occurrence of gastrointestinal complications in Marfan syndrome have appeared infrequently in the medical literature. In this review article we focus on both st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 43 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…The mutation in the fibrillin gene results in weakened connective tissues throughout the body, leading to varying multisystem dysfunction for those with Marfan syndrome [2, 6]. While Marfan syndrome causes abnormal findings manifest in many systems, gastrointestinal presentations are infrequent and there are only a few cases reported of differing diagnoses, most of the cases presenting with abnormal anatomy of various segments of the gastrointestinal system such as diverticulosis coli, hernias, diveriticula, atresias, malrotations and sigmoid volvulus [1, 3, 79].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The mutation in the fibrillin gene results in weakened connective tissues throughout the body, leading to varying multisystem dysfunction for those with Marfan syndrome [2, 6]. While Marfan syndrome causes abnormal findings manifest in many systems, gastrointestinal presentations are infrequent and there are only a few cases reported of differing diagnoses, most of the cases presenting with abnormal anatomy of various segments of the gastrointestinal system such as diverticulosis coli, hernias, diveriticula, atresias, malrotations and sigmoid volvulus [1, 3, 79].…”
Section: Discussionmentioning
confidence: 99%
“…Our patient’s history was significant for extensive cardiovascular involvement including mechanical aortic valve and mitral valve replacement, but no previous gastrointestinal involvement was noted. Upon review of the literature, there have been a few reported cases of small bowel diverticulosis, especially of the jejunal area, and a few reported cases of sigmoid volvulus in conjunction with a diagnosis of Marfan syndrome [3, 7, 8]. Jejunal volvulus reported was in a patient with no known history of Marfan syndrome and was likely due to massive jejunal diverticula from unknown cause ranging from 3.5 to 8 cm [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations